Erosive potential of different types of grape juices - Ginna Kércia Matos Gonçalves; Camila de Almeida Brandão Guglielmi; Fernanda Nahás Pires Corrêa; Daniela Prócida Raggio; Maria Salete Nahás Pires Corrêa (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The purpose of the present study was to evaluate the erosive potential of different types (concentrated and powdered) and commercial brands of industrialised grape juices. The pH of all five fruit drinks was measured at two time points: immediately after preparation and 24 hours later. Sixty specimens of bovine enamel were randomly allocated and immersed in different types of grape juice (n = 10) for 10 minutes four times a day for fifteen days. The enamel alteration was analysed using surface Knoop microhardness (KHN) and surface roughness (Ra) tests at baseline and on the 5th, 10th and 15th days of the experiment. Two way ANOVA, Tukey's post hoc and Pearson's correlation tests were used for statistical analysis (α = 5%). The grape juices presented pH values ranging from 2.9 to 3.5. All of the tested juices promoted significant enamel mineral loss (p < 0.05) on the first evaluation (5th day of immersion) and produced a significant increase in the mean roughness from the 10th day on when compared to the control group (p < 0.05). By the 15th day, all of the beverages had produced surface roughnesses that were significantly higher than that of the control group. The results suggest that all grape juices, regardless of their commercial presentation, present erosive potential.